1997
DOI: 10.1016/s0014-5793(97)01422-1
|View full text |Cite
|
Sign up to set email alerts
|

Chain termination codons and polymerase‐induced frameshift mutations

Abstract: The consensus sequence for single-base deletions in non-reiterated runs during in vitro DNA-dependent DNA polymerisation is refined using data available in the literature. This leads to the observation that chain termination codons are hotspots for single-base deletions. The evolutionary implications are discussed in two models which differ in whether polymerases evolved while the genetic code emerged or after the genetic code was fixed. A possible answer to the question 'Why are stop codons just what they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…This hypothesis of mutations directed at stop codons is in line with observations that polymerase errors are more frequent in stop codon contexts, interpreted as an adaptational bias to introduce mutations in stops [75]. In the next section, GenBank is explored to detect further mitogenomes in which genetic codes were switched by producing stop codons in ORFs and stop-depletion in other frames.…”
Section: Mechanisms That Switch Between Genetic Codes?supporting
confidence: 52%
“…This hypothesis of mutations directed at stop codons is in line with observations that polymerase errors are more frequent in stop codon contexts, interpreted as an adaptational bias to introduce mutations in stops [75]. In the next section, GenBank is explored to detect further mitogenomes in which genetic codes were switched by producing stop codons in ORFs and stop-depletion in other frames.…”
Section: Mechanisms That Switch Between Genetic Codes?supporting
confidence: 52%
“…Single base changes, especially transitions, usually cause either no amino acid change or the change to a chemically similar amino acid. In more recent works, Jestin and Kempf (1997) showed that the codon assignment of stop signals optimized the tolerance of polymerase-induced frameshift mutations, that is, most singlebase deletions are less deleterious at chain termination codons than at codons encoding amino acids. Furthermore, the work of Ardell and Sella (2002) using a population genetic model of code-message coevolution demonstrated that such coevolution tends to produce structure-preserving codes, and in particular it can reproduce some of the structure-preserving patterns of the standard 3 A c c e p t e d m a n u s c r i p t genetic code.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The nucleotide triplets TAA, TAG, TGA, which function as termination codons in translation, are hotspots for single nucleotide deletions during polymerization (Jestin and Kempf, 1997). Putatively, these frameshift mutation signals could have become translation termination signals.…”
Section: Introductionmentioning
confidence: 99%